BIMBINGAN KELOMPOK DENGAN TEKNIK PERMAINAN TRADISIONAL UNTUK MENINGKATKAN PENYESUAIAN SOSIAL - Dinar Mahdalena Leksana (Universitas Islam Lamongan, 2017)
This study aims to: (1) find out the implementation of group guidance and social adjustment level of grade 1 students of SDN Kedondong 01, (2) know the effectiveness of group guidance with traditional games to improve students' social adjustment. This is a quantitative research using pre-test post-test one group design. The data analysis technique used is Wilcoxon's Signed Rank Test which belongs to non parametric statistic. Based on the significant level 5% and N = 8 data analysis showed difference of scores between before and after implementing group guidance with traditional games technique. The result of field test shows that the group guidance model with traditional learning technique is effective to improve social adjustment of grade I students of SDN Kedondong 01. This is indicated by the change of social adjustment level of students before and after the implementation. that is an increase of 19%. Therefore it could be suggested to the counselor in elementary school to improve the utilization of traditional games in the implementation of group guidance as such a legacy to the scientific development.